2016
DOI: 10.1021/acs.nanolett.6b02858
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Siloxane Chirality on Twisted and Helical Nanometric Amorphous Silica

Abstract: Synthesis of chiral inorganic or hybrid nanomaterials through sol-gel transcription of chiral organic templates has attracted a great deal of interest for more than a decade. However, the chiral nature of these inorganic matrices has never been directly observed. For the first time, we report a direct evaluation of chirality on noncrystalline silica chiral nanoribbons by vibrational circular dichroism (VCD) measurements. Strong Cotton effect around 1150-1000 cm from Si-O-Si asymmetric stretching vibration was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 33 publications
0
45
0
Order By: Relevance
“…(c) Illustration of twisted and helical silica nanoribbons and their VCD spectra from ref. . Reprinted with permission from reference , Copyright, 2012, American Chemical Society.…”
Section: Enantiomerically Enriched Asymmetric Silica With Chiropticalmentioning
confidence: 99%
See 2 more Smart Citations
“…(c) Illustration of twisted and helical silica nanoribbons and their VCD spectra from ref. . Reprinted with permission from reference , Copyright, 2012, American Chemical Society.…”
Section: Enantiomerically Enriched Asymmetric Silica With Chiropticalmentioning
confidence: 99%
“…Afterwards, several studies were reported that used different helical templates self‐assembled from chiral molecules to prepare outward helical silica (spring‐type) with precise helical pitches from 10 to 100 nm . Figure shows an example of a helical silica obtained from a sol‐gel reaction in the presence of lipid nanoribbons . In addition to (spring‐type) helical chirality, sol‐gel methods are also used to prepare silica with the chiral nematic order by using the self‐assembled chiral lyotropic liquid‐crystalline phase (nematic‐type) as templates .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these studies, chiral semiconductor materials are extraordinarily important because of their various energy gaps, which enhance their absorption ranging from ultraviolet to near infrared region. Thereby, the optical activity (OA) can be effectively investigated by direct focus on the interaction between light with chiral semiconductors, such as electronic‐based circular dichroism and vibrational circular dichroism . As an important p‐type transition‐metal oxide with a narrow band gap ( E g = 1.2 eV), CuO has been extensively studied due to its important properties and applications …”
Section: Introductionmentioning
confidence: 99%
“…Chiral inorganic materials have attracted considerable attention for over 15 years because of their unique optical activity and potential applications in many elds, such as chiral catalysis, optical separation, and chiral sensors. [1][2][3][4][5][6] Among them, particularly, the preparation and application of chiral materials in relation to metallic nanoparticles (NPs) helped to clarify the potential of the plasmonic feature of the NPs. There are several approaches to imparting the chiroptical property to the metallic NPs.…”
Section: Introductionmentioning
confidence: 99%